ANALISIS ISI PEMBERITAAN TEWASNYA OSAMA BIN LADEN PADA SURAT KABAR KOMPAS DAN MEDIA INDONESIA - Sihabudin, Fikri (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2012)
Every media has agenda that setting in the media content. Kompas and Media Indonesia are the major newspa-per in Indonesia, on Mei 2011 both media published several news about Osama Bin Laden Death. This reseach focusing how Osama Bin Laden Death news at Kompas and Media Indonesia on Mei 2011. Content analysis is the method to analysis content news in newspaper. Research method is kuantitative with content analysis :news frekuensy,pages, article colum, paragraf, informant, cover both side.